The value of the expression $1.\left( {2 - \omega } \right)\left( {2 - {\omega ^2}} \right) + 2.\left( {3 - \omega } \right)\left( {3 - {\omega ^2}} \right) + ............. + \left( {n - 1} \right)\left( {n - \omega } \right)\left( {n - {\omega ^2}} \right)$ where $\omega $ is an cube root of unity is
$
(a){\text{ }}{\left\{ {\dfrac{{n(n + 1)}}{2}} \right\}^2} \\
(a){\text{ }}{\left\{ {\dfrac{{n(n + 1)}}{2}} \right\}^2} - {\text{n}} \\
(a){\text{ }}{\left\{ {\dfrac{{n(n + 1)}}{2}} \right\}^2} + {\text{n}} \\
(a){\text{ None of the above}} \\
$
Answer
Verified
510.6k+ views
Hint: In this problem we have to evaluate the given expression and it has been given that $\omega $ is the cube root of units. Let’s understand what does a cube root of unity means the solution of ${\left( 1 \right)^{\dfrac{1}{3}}} = \left( {1,\omega ,{\omega ^2}} \right)$, thus $\omega $ is known as cube root of unit. Use the various properties of cube root of unity like $\left( {1 + \omega + {\omega ^2} = 0} \right){\text{ & }}\left( {{\omega ^3} = 1} \right)$ along with the formula for sum of squares of first n natural numbers to get the answer.
Complete step-by-step answer:
Given expression is
$1.\left( {2 - \omega } \right)\left( {2 - {\omega ^2}} \right) + 2.\left( {3 - \omega } \right)\left( {3 - {\omega ^2}} \right) + ............. + \left( {n - 1} \right)\left( {n - \omega } \right)\left( {n - {\omega ^2}} \right)$
Now it is given that $\omega $ is an imaginary cube root of unity
Therefore $\left( {1 + \omega + {\omega ^2} = 0} \right){\text{ & }}\left( {{\omega ^3} = 1} \right)$
Now the first term of the series is
$1.\left( {2 - \omega } \right)\left( {2 - {\omega ^2}} \right)$
Now simplify it we have,
$1.\left( {2 - \omega } \right)\left( {2 - {\omega ^2}} \right) = 4 - 2{\omega ^2} - 2\omega + {\omega ^3} = 4 - 2\left( {\omega + {\omega ^2}} \right) + {\omega ^3}$
Now substitute the value of $\left( {\omega + {\omega ^2}} \right)$ which is -1 and the value of ${\omega ^3}$ which is 1.
$ \Rightarrow 1.\left( {2 - \omega } \right)\left( {2 - {\omega ^2}} \right) = 4 - 2\left( { - 1} \right) + 1 = 7$
$ \Rightarrow 1.\left( {2 - \omega } \right)\left( {2 - {\omega ^2}} \right) = {2^3} - 1$
Now the second term of the series is $2.\left( {3 - \omega } \right)\left( {3 - {\omega ^2}} \right)$
Now simplify it we have,
$ \Rightarrow 2.\left( {3 - \omega } \right)\left( {3 - {\omega ^2}} \right) = 2\left( {9 - 3{\omega ^2} - 3\omega + {\omega ^3}} \right) = 2\left( {9 - 3\left( { - 1} \right) + 1} \right) = 2\left( {13} \right) = 26$
$ \Rightarrow 2.\left( {3 - \omega } \right)\left( {3 - {\omega ^2}} \right) = {3^3} - 1$
Similarly ${n^{th}}$ term of the series is $\left( {{n^3} - 1} \right)$
So, the series converted into
$\left( {{2^3} - 1} \right) + \left( {{3^3} - 1} \right) + .................. + \left( {{n^3} - 1} \right)$
Now the sum of this series is
${S_n} = \sum\limits_{r = 1}^n {\left( {{r^3} - 1} \right)} $
$ \Rightarrow {S_n} = \sum\limits_{r = 1}^n {{r^3} - } \sum\limits_{r = 1}^n 1 $
Now as we know summation of $\sum\limits_{r = 1}^n {{r^3}} = {\left( {\dfrac{{n\left( {n + 1} \right)}}{2}} \right)^2}$ and $\sum\limits_{r = 1}^n 1 = n$
So substitute these values in above equation we have,
$ \Rightarrow {S_n} = {\left( {\dfrac{{n\left( {n + 1} \right)}}{2}} \right)^2} - n$
So this is the required answer.
Hence, option (b) is correct.
Note: Whenever we face such types of problems involving cube root of unity the key point is to have a good grasp over the formula involving cube root of unity, some of which are mentioned above. The basic understanding about the definition of the cube root of unity along with formula implementation after simplification will help you get on the right track to reach the answer.
Complete step-by-step answer:
Given expression is
$1.\left( {2 - \omega } \right)\left( {2 - {\omega ^2}} \right) + 2.\left( {3 - \omega } \right)\left( {3 - {\omega ^2}} \right) + ............. + \left( {n - 1} \right)\left( {n - \omega } \right)\left( {n - {\omega ^2}} \right)$
Now it is given that $\omega $ is an imaginary cube root of unity
Therefore $\left( {1 + \omega + {\omega ^2} = 0} \right){\text{ & }}\left( {{\omega ^3} = 1} \right)$
Now the first term of the series is
$1.\left( {2 - \omega } \right)\left( {2 - {\omega ^2}} \right)$
Now simplify it we have,
$1.\left( {2 - \omega } \right)\left( {2 - {\omega ^2}} \right) = 4 - 2{\omega ^2} - 2\omega + {\omega ^3} = 4 - 2\left( {\omega + {\omega ^2}} \right) + {\omega ^3}$
Now substitute the value of $\left( {\omega + {\omega ^2}} \right)$ which is -1 and the value of ${\omega ^3}$ which is 1.
$ \Rightarrow 1.\left( {2 - \omega } \right)\left( {2 - {\omega ^2}} \right) = 4 - 2\left( { - 1} \right) + 1 = 7$
$ \Rightarrow 1.\left( {2 - \omega } \right)\left( {2 - {\omega ^2}} \right) = {2^3} - 1$
Now the second term of the series is $2.\left( {3 - \omega } \right)\left( {3 - {\omega ^2}} \right)$
Now simplify it we have,
$ \Rightarrow 2.\left( {3 - \omega } \right)\left( {3 - {\omega ^2}} \right) = 2\left( {9 - 3{\omega ^2} - 3\omega + {\omega ^3}} \right) = 2\left( {9 - 3\left( { - 1} \right) + 1} \right) = 2\left( {13} \right) = 26$
$ \Rightarrow 2.\left( {3 - \omega } \right)\left( {3 - {\omega ^2}} \right) = {3^3} - 1$
Similarly ${n^{th}}$ term of the series is $\left( {{n^3} - 1} \right)$
So, the series converted into
$\left( {{2^3} - 1} \right) + \left( {{3^3} - 1} \right) + .................. + \left( {{n^3} - 1} \right)$
Now the sum of this series is
${S_n} = \sum\limits_{r = 1}^n {\left( {{r^3} - 1} \right)} $
$ \Rightarrow {S_n} = \sum\limits_{r = 1}^n {{r^3} - } \sum\limits_{r = 1}^n 1 $
Now as we know summation of $\sum\limits_{r = 1}^n {{r^3}} = {\left( {\dfrac{{n\left( {n + 1} \right)}}{2}} \right)^2}$ and $\sum\limits_{r = 1}^n 1 = n$
So substitute these values in above equation we have,
$ \Rightarrow {S_n} = {\left( {\dfrac{{n\left( {n + 1} \right)}}{2}} \right)^2} - n$
So this is the required answer.
Hence, option (b) is correct.
Note: Whenever we face such types of problems involving cube root of unity the key point is to have a good grasp over the formula involving cube root of unity, some of which are mentioned above. The basic understanding about the definition of the cube root of unity along with formula implementation after simplification will help you get on the right track to reach the answer.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE